敘述七○年代：離鄕、祭國、資本化 - 王智明 (國立陽明交通大學出版社, 2007)
在九○年代的敘述裡，七○年代似乎被記憶成一個理想主義的年代，在資本洪流四處滾的今天，承載著不少的懷舊情緒。無論是像《玻璃之城》這樣的商業電影，或是像「珍藏美麗島」之類的口述歷史，還是像《思想》雜誌這樣的文化論述，七○年代似乎是一個充滿著美麗、哀愁、純真與熱情的年代。在這些紛雜的敘述裡，七○年代對兩岸三地的華人來說，究竟代表了什麼樣的集體記憶與歷史意識，它又反映了怎麼樣的歷史結構？重訪七○年代能夠為紛亂矛盾的今天帶來什麼樣的啓示？ 劉大任與張系國的小說，楊澤為《中國時報》人間副刊主編的「七○年代」專輯，《思想》雜誌的「台灣七十年代」專題，與《九十年代》這本海外華人思想雜誌的休刊，分別代表了敘述七○年代的不同嘗試，與建構七○年代歷史意識的不同方法。將在不同時期與地域出版的文本與敘事拉扯在一起，本文以年代與世代為兩條交錯卻不相同的軸線來重述七○年代在不同地域及文本的意義。藉著游走於香港、台灣及海外等地的七○年代敘述，本文提出「華人七○年代」和「跨太平洋反抗世代」等概念，並討論隱身於其後複雜的歷史脈絡與情感糾葛，以指出國族視角的局限，以及跨國華人視野對於七○年代敘述的重要性。透過分析這些不同的敘述，本文企圖尋找一條「進入」七○年代的路徑。進入，不是為了重回歷史現場－畢竟過去無法完整重現－而是希望在記憶的封存與開啟之際，掌握歷史真實而複雜的面貌，並在不斷敘述的同時，重新思考七○年代作為一個批判方案的可能性與意義。

In the narratives about the 1970s, the 1970s is remembered as an age of idealism, which carries a sense of nostalgia against the bleak background of late capitalism. Whether it is remembered in such commercial films as Boli zhi cheng (City of Glass), in the sort of oral history as ”Zhengchang meilidao” (Treasuring Formosa), or in the cultural critique of Sixiang (Thought), the 1970s is portrayed as an age painted with beauty, remorse, innocence and passion. In the myriad of narratives, what collective memory and historical consciousness does the 1970s signify for the ”Chinese” people living in Hong Kong, Taiwan and the U.S.? How do these diverse narratives about the 1970s reflect the historical structure of the time? By revisiting the 1970s, what lessons are to be gained for today? The novels of Liu Daren and Zhang Xiguo, China Times' special issue on the 1970s, Thought Magazine’s special issue on the ”Taiwanese 1970s,” as well as the last issue of The 1990s (Jiushiniandai) represent different attempts at narrating the 1970s and thus diverse ways of constructing historical consciousness. Linking together these narratives about the 1970s in North America, Taiwan and Hong Kong, I take generation and period to be two dissimilar but intersecting concepts for understanding the significance of the 1970s. By raising such ideas as the ”Chinese 1970s” and the ”transpacific generation of resistance,” this article discusses the complex historical and emotional entanglements and points out the limitation of national historiography as texts of selective memories. Through a critical analysis of these interconnected narratives about the 1970s, it seeks to carve an ”access” into the 1970s, not to restore the so-called historical truth, but to explore and capture the complexities of the 1970s as a critical historical moment. Its fruitful possibilities suggest the importance of seizing the 1970s as a critical project for the present.
Keywords: 華人七○年代; 跨太平洋反抗世代; 歷史意識; 斷代思維; 敘述的政治; 保釣運動; the Chinese 1970s; the transpacific generation of resistance; historical consciousness; periodization; politics of narration; the Baodiao movement